AN ANALYSIS OF MATERIALS IN A STUDENT TEXTBOOK AT SECONDARY SCHOOL IN 8th GRADE - Simorangkir, Raja Daud; Naibaho, Tumiur Ririn Afriani; Sinambela, Pennalia; Panjaitan, Chyntia Tiodora (JEE (Journal of English Education), 2019)
Learning English is very important for education because English is one of the most used language in the world. This paper was conducted to students 8th secondary school. The findings of the English On Sky 2 By Erlangga to find out whether be English text book use for the secondary school. This book developed the skills suggested by the school-based curriculum and communicative exercises. The second book is Bahasa Inggris Communicative English in Context by Grafindo. This book discusses written and interpersonal text interaction learning material. The third book is When English Rings a Bell by PT Gramedia. In this book students are invited to boldly seek other learning resources available and within reach.. After learn these books the students can increase their knowledge about English education.